Separation of Enantiomers. - Todd, Matthew H. (Wiley-VCH, 2014)
In one handy volume this handbook summarizes the most common synthetic methods for the separation of racemic mixtures, allowing an easy comparison of the different strategies described in the literature. Alongside classical methods, the authors also consider kinetic resolutions, dynamic kinetic resolutions, divergent reactions of a racemic mixture, and a number of ""neglected"" cases not covered elsewhere, such as the use of circularly polarized light, polymerizations, ""ripening"" processes, dynamic combinatorial chemistry, and several thermodynamic processes. The result is a thorough introdu.